Managing Marine Litter: Exploring the Evolving Role of International and European Law in Confronting a Persistent Environmental Problem - Trouwborst, Arie (Utrecht Journal of International and European Law, 2011)
The contamination of the world's oceans by human garbage, especially plastics, ranks among those environmental problems whose resolution appears remote, despite the considerable public attention paid to the 'Great Garbage Patch' in the Pacific, 'plastic soup', and the like. This 'marine litter' (or 'marine debris') problem is characterized by diffuse sources and an array of adverse environmental impacts, including entanglement of and ingestion by albatrosses, fulmars, turtles, seals and a variety of other marine wildlife. This article explores the evolving role of international law in the efforts to manage marine litter, including recent developments involving the Convention for the Protection of the Marine Environment of the North-East Atlantic (OSPAR Convention) and the European Union's Marine Strategy Framework Directive (MSFD).